Study on topographical distribution of carcinoma larynx (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the sites of involvement of carcinoma larynx. Methods: A cross sectional study was carried out from January, 2006 to December, 2007 at the Department of ENT and Head-Neck Surgery of Dhaka Medical College Hospital, Dhaka. This study included 147 cases with of carcinoma larynx. Results: Among 147 cases in this study near age was 54.53 years the pearl incidence was 6th to 7th decade; male: female rate 28.4: 1. Majority of case were related to cultivation (42.6%), came for rural area (66.7%), socioeconomic group (68%) and illiterate (49.7%). Regarding habit most of them were more than one habits (87.7%) patients were smokers, duration of smoking habit varied from 2 years to more than 40 years and per day consumption from 3-32 sticks. 100% of female had the, habit of betel leaf chewing in this study. The common symptom was hoarseness of voice (93.8%) followed by dysphagia (61.6%) respiratory distress (52.4%), earache (6.8%) cases, haemoptysis and neck pain in small proportion. Indirect larygoscopic examination: Supraglottic carcinoma extension to one dial wall of pyriform fossa and valecular / bare of the tongue were present in (11.5%) and 8.7 cases respectively. 73.4% cases were more then one subsites involvement. Impaired vocal cord morbidity was found in 30.9% and fixed cord was 49.6%, 55.2% cases were airway inadequate, nodal involvement was 46.9%, 98.6% nodal involvement in supraglotic region, 65.2% were NI stage followed by N2 (21.7% and N3 (13%) distribution of the carcinoma larynx were supraglottic 74.10 glottic 25.10% and subglottic 0.70% more than one insite involvement were 88%, in supraglottic epiglottis 5.5%, any epiglottic folds 4.6% or glend 0.9% and ventricular bands were 0.9%. In the subsite of the glottic carcinoma glottic proper 37.8% followed by more then one insite (32.4%) anterior commissure 18.4% and posterior commissure 10.8%, 55% of the patient were Grade II and 49.6% were stage III. Conclusion: Incidence of supraglottic carcinoma was more common, involvement of more than one single site also common. Key words: Carcinoma larynx; supraglottic. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8848 BJO 2011; 17(2): 96-103